2006
DOI: 10.1063/1.2402963
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative doping effects of Ti and C on critical current density and irreversibility field of MgB2

Abstract: Carbon and titanium concurrently doped MgB 2 alloys with a composition of Mg 1−x Ti x B 2−y C y have been prepared by an in situ solid state reaction method. The combination effects of carbon and Ti doping on structure, microstructure, irreversibility field ͑H irr ͒, and critical current density ͑J c ͒ of MgB 2 have been investigated. It is found that doping Ti in MgB 2 does not reduce the solubility of carbon in MgB 2 , but, on the contrary, it eliminates the porosity present in the carbon-doped MgB 2 , resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
2
14
1
Order By: Relevance
“…These results indicated that higher J c could be obtained in the MgB 2 samples with metals and C-based chemical co-doping [12][13][14]. However, there is still no study on the metal and sugar co-doped MgB 2 superconductors till now.…”
Section: Introductionmentioning
confidence: 58%
“…These results indicated that higher J c could be obtained in the MgB 2 samples with metals and C-based chemical co-doping [12][13][14]. However, there is still no study on the metal and sugar co-doped MgB 2 superconductors till now.…”
Section: Introductionmentioning
confidence: 58%
“…As shown in Fig. 1, the pure sample has a T c of 38.0 K and a sharp transition width ( T ) which indicates a good quality and chemical homogeneity [2,8]. It is clearly seen that with increasing C 4 H 6 O 5 addition, transition temperatures decrease and transition widths increase.…”
Section: Resultsmentioning
confidence: 86%
“…All these applications require high current density (J c ) under magnetic field and high magnetic levitation force capacity. However, many studies indicate that one of the problems of MgB 2 is that the current density, J c , values fall sharply with increasing magnetic field due to weak flux pinning and chemical heterogeneity at grain boundaries [6][7][8][9][10][11]. Great effort has been done to improve levitation force and critical current density of bulk MgB 2 materials under magnetic fields by methods, such as elemental addition or doping, thermo-mechanical processing, or by proton irradiation.…”
Section: Introductionmentioning
confidence: 98%
“…In order to solved problem mentioned above, Ti and carbon concurrent doping was developed [6,7]. The experimental results clearly reveal that carbon and Ti concurrent-doping is largely cooperative in improving the performance of MgB 2 in the high magnetic fields (>3 T) and at high temperature (>20 K).…”
Section: Introductionmentioning
confidence: 97%